2018
DOI: 10.1108/jme-05-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Parental expectations of and satisfaction with the services of preschool centres

Abstract: Purpose-This paper aims to study parental expectations of and satisfaction with overall services of preschool centres and to determine the factors which affect parents' satisfaction in a part of one of Thailand's southern provinces. Design/methodology/approach-Data were collected using a structured questionnaire from parents of children attending 29 day-care or preschool centres in Songkhla Province, South Thailand, over a two-month period in the Spring 2014. The data were analysed mainly using descriptive sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…He also notes that in Vietnam, three quarters of children attend pre-school in urban areas but only about half do in rural areas. Compared to that baseline, Thailand's Songkhla province, the location of the Prayukvong et al [1] study, was found to be doing quite well but one is assured that provision is not similarly good across all Thai provinces.…”
Section: Global Journal Of Intellectual and Developmental Disabilitiesmentioning
confidence: 80%
See 1 more Smart Citation
“…He also notes that in Vietnam, three quarters of children attend pre-school in urban areas but only about half do in rural areas. Compared to that baseline, Thailand's Songkhla province, the location of the Prayukvong et al [1] study, was found to be doing quite well but one is assured that provision is not similarly good across all Thai provinces.…”
Section: Global Journal Of Intellectual and Developmental Disabilitiesmentioning
confidence: 80%
“…
In a recent paper, my co-authors and I examined issues around the adequacy of both provision and quality of pre-school education in one province of Thailand, Prayukvong, Sornprasith and Foster [1]. As a final conjecture, I wrote (p.264), that, "one would speculate that, sadly, the opportunities and needs of disabled children, be they physical or mental disabilities, are likely to be somewhere rather low down the priorities list of many funders and providers, in a setting of intrinsic shortage.
…”
mentioning
confidence: 99%